DOP15 Fluorescent labelled vedolizumab for real-time visualization and quantification of local drug distribution and pharmacodynamics in Inflammatory Bowel Diseases during endoscopy. (21st January 2022) - Gabriëls, R Y; Linssen, M; van der Waaij, A; Volkmer, P; Hooghiemstra, W; Kats-Ugurlu, G; Robinson, D; Dijkstra, G; Nagengast, W
Abstract: Background: Vedolizumab is a monoclonal antibody which blocks integrin α4β7 inhibiting trafficking of T-lymphocytes into the gut. Unfortunately, up to 60% of vedolizumab patients experience non-response. The mechanism of action of vedolizumab is not elucidated, predictors of response are unknown and data for local drug distribution in the gut are lacking. In this clinical trial, we investigated the feasibility of assessing local distribution of fluorescently labelled vedolizumab in the gut mucosa of inflammatory bowel diseases (IBD) patients to finally enable prediction of therapy response in individual patients. Methods: Vedolizumab (Entyvio, Takeda Pharma) was labelled to IRDye 800CW under cGMP conditions to yield clinical grade vedolizumab-800CW. In this dose-escalation trial, vedolizumab naïve IBD patients and IBD patients treated with vedolizumab for at least 14 weeks were included. Patients received an intravenous dose of fluorescently labelled vedolizumab of either 0 mg, 4.5 mg, 15 mg or 15 mg + 75 mg unlabelled vedolizumab 3 days prior colonoscopy. In vivo fluorescence imaging was assessed by fibre-based wide-field fluorescence molecular endoscopy (FME) and quantified by spectroscopy in healthy, mildly inflamed and severely inflamed tissue. All assessed tissue was biopsied for ex vivo examination of the fluorescent signal, fluorescence microscopy and spectroscopy. Results: Up to submission 34 patients completed tracer injection and FME. An interim analysis was performed after 20 patients (5 in each dose group), which showed in severely inflamed tissue an 8 fold higher fluorescent signal in the 15 mg dose group (0.049 Q*μfa, x [mm-1]) compared to the control group (0.006 μfa, x [mm-1]) (p<0.05). Furthermore, the fluorescent signal within the 15 mg dose group was also 2.5 fold higher compared to healthy tissue (0.019 Q*μfa, x [mm-1]) (p<0.05).The addition of unlabelled vedolizumab gave similar results to the 15 mg group (p>0.99), suggesting that the drug target was still not saturated. The optimal dosage group of 15 mg was expanded up to 18 IBD patients, amongst them 6 IBD patients after 14 weeks of treatment regimen. Fluorescence microscopy showed clustering of fluorescent signals especially in inflamed mucosa. Additional experiments to detect vedolizumab target cells are ongoing. Conclusion: In vivo visualization of fluorescent vedolizumab revealed a clear dose-dependent correlation between mucosal drug concentrations and the severity of mucosal inflammation. Fluorescence molecular endoscopy is a promising novel tool to get insight in drug distribution in IBD, detect target cells, assess target engagement and possibly predict therapy response in individual patients.